Construction of heterojunctions between ReS2 and twin crystal ZnxCd1−xS for boosting solar hydrogen evolution. (3rd March 2021) - Guo, Luyan; Yu, Guiyang; Zhao, Haitao; Xing, Chuanwang; Hu, Yujia; Chen, Ting; Li, Xiyou
Abstract : Nanoflower-like ReS2 anchoring on nanotwins Zn x Cd1− x S greatly boosts photocatalytic hydrogen evolution rate with 31-times higher than pure phase P-ZCS. Abstract : Facilitating charge separation as well as surface redox reactions is considered to be an efficient way to improve semiconductor-based photocatalytic hydrogen generation. In this study, we developed a highly active and reliable photocatalyst, ReS2 /T-ZCS, by anchoring nanoflower-like ReS2 particles on the surface of host chalcogenide nanotwins (Zn0.5 Cd0.5 S). By virtue of the in-built driving force from the homojunction with a type-II staggered band alignment in twin crystal Zn0.5 Cd0.5 S (T-ZCS) and heterojunctions between T-ZCS and ReS2 on the surface of the photocatalyst, a substantially improved charge separation and transfer property were achieved. Hence, the twin crystal Zn0.5 Cd0.5 S decorated nanoflower-like ReS2 exhibits a significantly improved photocatalytic H2 evolution rate of 112.10 mmol g −1 h −1 and the corresponding apparent quantum efficiency reaches 32.65% at 420 nm, which is 31 times larger than that of pure phase Zn0.5 Cd0.5 S. Our work not only couples the merits of homojunctions and heterojunctions to promote solar energy conversion, but also expands applications of the transition metal dichalcogenide (TMD) family in electrocatalysis, photothermal-catalysis and energy storage.